Cassava starch nanocomposite films reinforced with nanocellulose - Asmawi N.; Ilyas R.A.; Mohd Roslim M.H.; Rajeshkumar L.; Abotbina W.; Syafri E.; Jumaidin R.; Syafiq R.; Rafiqah S.A.; Ridwan R.; Jusoh S.M.; Mohamed Yusoff M.Z. (De Gruyter Open Ltd, 2024)
Recent researchers are keen on developing alternative bioplastic materials from renewable and eco-friendly sources to replace the materials obtained from crude oil and other petroleum-based sources. The measures for these replacements have been made continuously to create a sustainable future for the forthcoming generations. Researchers are focusing on bio-based alternatives due to their numerous benefits, including biodegradability, biocompatibility, nontoxicity, and structural flexibility. The main problem on the current bio-based material such as poly lactic acid, poly butylene succinate and poly L lactide, polyhydroxybuturate, and polyhydroxyalkalonates is the cost of production. Compare with cassava starch, the cost is much cheaper around 0.32 $/kg compare with other bio-based will cost around 1.2-2.4 $/kg. Conversion of biomass into useful materials has been the order of the day, as it reduces the cost of inventory and aims to develop a nature-derived material. The development of nanocomposites from biological sources has progressively experimented with the researchers and the deriving of polysaccharides such as starch, cellulose, and glycogen has aided the development of nanobiocomposites. Corn starch has been the dominant bioplastic material derived out of corn which can handle a variety of reinforcements and render a biocomposite material with better and enhanced properties. Cassava starch is the most economic and cheap polysaccharide derived from the cassava plant and has a greater potential to act as biopolymer material for the development of biocomposites. The development of cassava starch-based biocomposite film was widely used for a wide range of applications mainly for food packaging applications. This review focuses on the extraction, preparation, and properties of cassava starch from cassava plants. The properties of the cassava starch and its composites were also comprehensively dealt with. The development of biocomposite films based on cassava starch for food packaging applications has been reviewed along with the challenges associated with it. 2023 Walter de Gruyter GmbH, Berlin/Boston.